A STUDENT SUPPORT GUIDING FRAMEWORK TOWARDS IMPROVING GRADUATION RATES FOR A NURSING COLLEGE IN SOUTH AFRICA: A CASE STUDY DESIGN. - Skakane, Thembekile Purity; Mtshali, Ntombifikile Gloria; Ngcobo, Sandiso (Student's Journal of Health Research Africa, 2024)
Background: Student attrition poses a significant challenge to nursing education institutions, leading to health worker shortages in South Africa and globally. This occurs despite implementing student support interventions that appear not to be well-implemented, not escalated, and need organizational structures that enable it. Hence, the purpose of the study was to develop an intentional student support framework that could assist improve student outcomes. Methods: The process was informed by a prior mixed-method research approach that involved the participation of students and staff in the completion of questionnaires and interviews as stakeholders in a selected nursing college, employing a case study design. Results: The quantitative results showed poor pre-enrolment support, in particular participants from disadvantaged communities. Both quantitative and qualitative studies revealed good academic support. However, the qualitative studies highlighted organizational conditions, processes, and practices that hindered the provision of comprehensive support. Conclusions: Therefore, a well-coordinated, comprehensive, intentional, and policy-aligned student support guiding framework is presented in this article. Recommendations: The College should implement this comprehensive student support guiding framework across all its campuses to address the diverse needs of its student body and promote their success and well-being.